RAPID TESTING IN THE CONTEXT OF THE NATIONAL PLAN TO COMBAT SEXUALLY TRANSMITTED INFECTIONS IN THE POPULATION DEPRIVED OF LIBERTY: EXPERIENCE REPORT - dos Reis, Rosane Pereira; da Silva Machado, Mickaelly; Calheiros, Renée Leão; da Silva Duarte, Jefferson; da Rocha Sarmento de Azevedo, Andrea Marcia; de Sousa Cavalcante, Elicélia Tenório; de Arecippo, Renata Giovanna Lima Digues; Gusmão, Beatriz Rodrigues (Seven Editora, 2025)
The prison population is highly vulnerable to sexually transmitted infections (STIs) due to factors such as overcrowding, poor sanitation conditions, and risky practices. In this context, rapid testing has become an essential strategy for early diagnosis and immediate treatment, as recommended by the National Plan to Combat STIs in the Prison System. The objective of this study was to describe the daily experience of prison health staff in conducting rapid testing for HIV, syphilis, and viral hepatitis, highlighting the workflow, strategies used, and challenges faced. This is a descriptive experience report based on the care routine of a multidisciplinary primary care team in prisons in Alagoas, with direct observation, medical records, and discussions in internal meetings. Rapid testing is performed continuously, with pre- and post-test counseling, guaranteed confidentiality, and the adoption of biosafety measures. In addition to early case detection, the practice integrates educational initiatives aimed at prevention and stigma reduction. Challenges include initial resistance from some inmates, resource constraints, and the need for coordination with prison management and the external health network. The conclusion is that the systematic incorporation of rapid testing into routine care is a strategic tool for combating STIs in the prison system, contributing to health equity and fulfilling the constitutional right to comprehensive care. DOI: https://doi.org/10.56238/sevened2024.029-068